GC/MS and LC/MS Based Serum Metabolomic Analysis of Dairy Cows With Ovarian Inactivity - Bai, Yunlong; Song, Yuxi; Zhang, Jiang; Fu, Shixin; Wu, Ling; Xia, Cheng; Xu, Chuang (Frontiers in Veterinary Science, 2021)
Metabolic disorders may lead to the inactive ovaries of dairy cows during early lactation. However, the detailed metabolic profile of dairy cows with inactive ovaries around 55 days postpartum has not been clearly elucidated. The objective of this study was to investigate metabolic difference in cows with inactive ovaries and estrus from the perspective of serum metabolites. Serum samples were analyzed using GC-TOF-MS and UHPLC-QTOF-MS and were collected from 15 dairy cows in estrus and 15 dairy cows with inactive ovaries at 55–60 d postpartum. Differences in serum metabolites were identified using multivariate statistical analysis and univariate analysis. Thirty differentially abundant metabolites were identified between the two groups. In cows with inactive ovaries compared with cows in estrus, 20 serum metabolites were significantly higher while 10 metabolites were significantly lower. Pathway analysis indicated that the serum differential metabolites of multiparous cows in estrus obtained by the two metabolomics techniques were mainly involved in β-alanine metabolism and steroid biosynthesis metabolism, while other involved metabolic pathways were related to metabolism of glyoxylate and dicarboxylate metabolism; fructose and mannose; glutathione; glycerolipid; glycine, serine, and threonine; propanoate; retinol; and pyrimidine. This indicates that the abnormalities in glucose metabolism, lipid metabolism, amino acid metabolism, and glutathione metabolism of postpartum dairy cows obstructed follicular development.